Analisis Faktor-Faktor Penyebab Contract Change Order (CCO) Pada Proyek Konstruksi di Kota Palangka Raya - Yunisa, Salwa Inka; Puspasari, Veronika Happy (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2024)
In the implementation of construction projects, they are often faced with problems, one of which is the occurrence of changes. Changes such as Contract Change Orders have an impact on the implementation of construction projects which will increase or decrease time, costs and quality. This research was conducted on two groups of respondents to determine whether or not there were differences of opinion between contractor respondents and supervisory consultants. The first stage carried out was to identify the factors causing the Contract Change Order from a number of previous research journal articles. The second stage is distributing questionnaires to construction companies registered with the Palangka Raya City LPSE for 2020-2023. The third stage is processing the data using the SPSS computer application to test validity and reliability, before analyzing it using Descriptive Analysis to determine the ranking of dominant factors. Then a Difference Test (Mann-Whitney) was carried out to determine the differences in opinion between the contractor respondent group and the supervisory consultant. The research was conducted in August-November 2023. The results of the literature study show twenty factors that cause Contract Change Orders on construction projects in Palangka Raya City. Descriptive analysis shows that there are three dominant factors, namely (mismatch between drawings and field conditions; addition and subtraction of work items; and addition and reduction of work volume). The Difference Test (Mann-Whitney) shows the calculated Z value < Z table = -0.094 < 1.96. So H0 can be accepted, namely that there is no significant difference in the factors causing Contract Change Orders (CCO) between contractor experts and supervisory consultants